2010
DOI: 10.2478/v10045-010-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisia Annua L. On Deterrence and Nutritional Efficiency Of Lesser Mulberry Pyralid (Glyphodes Pylolais Walker) (lepidoptera: Pyralidae)

Abstract: Methanolic extract of Artemisia annua L. were evaluated on growth and nutritional efficiency of lesser mulberry pyralid Glyphodes pyloalis (Lepidoptera: Pyralidae) in laboratory conditions (24±1°C, 75±5% RH and 16 L : 8 D). Feeding deterrence index was evaluated by a choice test method on < 24 h fifth instar larvae with 5, 2.5, 1.25 and 0.625 percent of the extract. The result indicated that increasing the concentration resulted in higher deterrence. The extract retarded larval growth significantly (EC 50 = 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 29 publications
7
19
1
Order By: Relevance
“…In the present study, the activity of GST in larvae with the studied essential oil, decreased, compared to the control. Our results are different from the results obtained in other studies (Vanhaelen et al 2001;Dugravot et al 2004;Khosravi et al 2010;Zibaee and Bandani 2010b). In our study, the general esterase activity decreased in the H. armigera larva with the essential oil which we used.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, the activity of GST in larvae with the studied essential oil, decreased, compared to the control. Our results are different from the results obtained in other studies (Vanhaelen et al 2001;Dugravot et al 2004;Khosravi et al 2010;Zibaee and Bandani 2010b). In our study, the general esterase activity decreased in the H. armigera larva with the essential oil which we used.…”
Section: Discussioncontrasting
confidence: 99%
“…Also glucose depletion may be due to stress conditions imposed on these insects that need more energy, so the glucose was metabolized to meet the energy expense. Similar results were observed by Khosravi et al (2010) in G. pyloalis larva treated with A. annua extract, and by Seyoum et al (2002) in desert locust.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Liu and Ho (1999), Zapata et al (2009), andPavela et al (2009) also reported a reduction in feeding indices after treatment of their respective insects with plant extracts or essential oils. Lower RGR, RCR, and ECI probably lead to larval growth retardation and formation of smaller pupa, which results in reduced fecundity and longevity of the adult insect and makes them susceptible to diseases and natural enemies (Khosravi et al 2010). Also, reductions of nutritional indices of the 5 th instar larvae of Spodoptera littoralis (Boisduval) induced by Reynoutria sp.…”
Section: Discussionmentioning
confidence: 99%